2017
DOI: 10.1039/c7dt03710d
|View full text |Cite
|
Sign up to set email alerts
|

A platinum porphyrin modified TiO2 electrode for photoelectrochemical hydrogen production from neutral water driven by the conduction band edge potential of TiO2

Abstract: The onset potential for H production from neutral water (pH 7) catalyzed by a platinum(ii) porphyrin (PtP-py) modified TiO electrode positions very close to the standard water reduction potential (less than 50 mV). H production is driven by the conduction band edge potential of TiO at the PtP-py-modified TiO cathode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 35 publications
2
41
0
Order By: Relevance
“…NHE in aqueous solution (pH=7) according to our literature [31] and obtained as −0.80 V vs . NHE in aqueous solution (pH=12) since the CBE potential showed a linear pH dependence with the slope of 59 mV per pH unit [35] …”
Section: Resultsmentioning
confidence: 99%
“…NHE in aqueous solution (pH=7) according to our literature [31] and obtained as −0.80 V vs . NHE in aqueous solution (pH=12) since the CBE potential showed a linear pH dependence with the slope of 59 mV per pH unit [35] …”
Section: Resultsmentioning
confidence: 99%
“…Comparison with analogous phosphonate-derivatized [Ru(bpy) 3 ] 2+ complexes demonstrates improved surface stability in aqueous solution at pH 5. Another example was also reported by the same group, where a pyridine-derivatized platinum(II) porphyrin was used as an electrocatalyst for water reduction 21 .…”
Section: Introductionmentioning
confidence: 89%
“…Thus, PdTCP (H‐type) is the electron donor (photosensitizer) and PtTCP (J ‐ type) the electron acceptor (catalyst) in the mixed component catalytic system (PdTCP‐PtTCP/TiO 2 ). Sakai, Ozawa and co‐workers have reported that the H 2 evolution mechanism of a Pt porphyrin onto TiO 2 is based on two electron transfer processes [30] . It is very reasonable to consider that the H 2 production in our work also proceeds via two consecutive one‐electron processes.…”
Section: Resultsmentioning
confidence: 76%